Bentonite as a Potential Countermeasure against T-2 Toxin and Ochratoxin A (OA) in Chickens - Trapty Agarwal, Apoorva Narad, Nithya MS (Revista Electronica de Veterinaria, 2024)
The development of mycotoxins (MT), Ochratoxin-A (OA) and T-2 toxin (T-2T), in hen feeding is a major concern for the livestock business since it negatively impacts the nutrition and productivity of broiler chicks. The analysis focuses on a specific subset of MT and could not contain the whole spectrum of MT that chickens deal with real-world scenarios. In this analyze the beneficial impact of high-grade betonies (HGE) on broiler chicks that have been exposed to OA+T-2T, a mixture of both toxins. To examine the effects of adding bentonite (BE) to the diet of broiler chickens exposed to these MT, focusing on growing efficiency, organs weights and blood metabolic indicators. A combination of 336 Cobb broiler chicks (CBC) that were one day older were acquired from a professional breeder and distributed among several therapy categories. The blood samples were analyzed for the activities of gamma glutamyltransferase (GGR) and alanineaminotransferase (ALR). The analysis examined the effects of dietary amounts of Ochratoxin (OC) at 2 (ppm), T-2T at 3 (ppm) and HGE at 2% in a totally controlled approach. The administration of 2% HGE to feeds comprising OA, as well as the mixture of OA+T-2T, did not result in a substantial increase in physical weight at any age. Nevertheless, the group that received T-2T exhibited a substantial (P<0.05) enhancement in physical weight up to the fourth week of birth. The results of this investigation indicate that supplementing with HGE at the percentage tested did not effectively mitigate the negative impacts of OA+T-2T and their mixture in the feeds of broiler chickens.